2009
DOI: 10.1002/chem.200802590
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Role of Amines in the Synthesis of Molecular Sieves in Ionic Liquids

Abstract: A combination of state-of-the art in situ one- and two-dimensional NMR spectroscopy and density functional theory (DFT) calculations have been employed for the first time to investigate the role of amines in the synthesis of aluminophosphate molecular sieves in ionic liquids (ILs). In situ rotating-frame nuclear Overhauser effect spectroscopy (ROESY) was used to demonstrate that the hybrid of imidazolium ionic liquids with organic amines, such as morpholine, connected through a hydrogen bond can be formed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 54 publications
0
58
0
Order By: Relevance
“…For instance, research from our own and Dehnen's groups showed that a combination of ILs and an organic amine as auxiliary solvent was an efficient system for the fabrication of selenidostannates, in which the organic amine and the IL cations might co-induce specific structures. 24,25 Similar phenomena have been observed in the ionothermal syntheses of zeolites; [26][27][28][29] for example, a new open-framework aluminophosphate with a unique Al/P ratio was synthesized by using an amine and ILs as co-templates. 26, 29 Thus we realize that syntheses in ILs with different SDAs would produce highly novel structures due to the chemical and compositional flexibility of SDAs.…”
Section: Introductionmentioning
confidence: 63%
“…For instance, research from our own and Dehnen's groups showed that a combination of ILs and an organic amine as auxiliary solvent was an efficient system for the fabrication of selenidostannates, in which the organic amine and the IL cations might co-induce specific structures. 24,25 Similar phenomena have been observed in the ionothermal syntheses of zeolites; [26][27][28][29] for example, a new open-framework aluminophosphate with a unique Al/P ratio was synthesized by using an amine and ILs as co-templates. 26, 29 Thus we realize that syntheses in ILs with different SDAs would produce highly novel structures due to the chemical and compositional flexibility of SDAs.…”
Section: Introductionmentioning
confidence: 63%
“…However, in the previous enzymatic synthesis of FGs, excess glycerol or organic solvents were required as reactants and solvents to obtain high FGs yields [9,13,15,16]. To overcome these disadvantages, ionic liquids (ILs), due to their negligible vapor pressure, high thermal stability for enzyme, and favorable solvating property (molecular sieve role) for particular components [17][18][19][20][21], have been used as an alternative green reaction medium for many enzymatic reactions. Previously, we developed a novel IL ([EMIM]TF 2 N) system for lipase-catalyzed DFG production with ∼100% EF conversion and 45% DFG yield [11].…”
Section: Introductionmentioning
confidence: 99%
“…Under nonhydrothermal conditions, this question becomes even more pertinent. [9][10][11][12] To date, a number of in situ crystallization studies probing microporous aluminophosphate synthesis exist, the majority of which focus on (Co)APO-5 (AFI structure). These studies utilize mostly scattering methods for probing the onset of crystallization, although many also employ spectroscopic techniques allowing for atomic/molecular insight into the self-assembly process.…”
Section: ' Introductionmentioning
confidence: 99%